Bringing the OhioHealth Nursing Strategic Plan to Life With the AONE Care Innovation and Transformation Program. (December 2017) - Dials, Kelly; Gossett, Lisa; Osting, Lindsey; Rutherford, David; Stifter, Janet
Abstract : Contemporary CNOs are committed to developing the next generation of nurse leaders. At OhioHealth, the nursing strategic vision includes the belief that every nurse will be a leader in improving health across the care continuum. In 2016, the OhioHealth System partnered with AONE to participate in the Care Innovation and Transformation program resulting in bedside nurses living this strategic vision and creating positive changes in quality, safety, and satisfaction for patients and families.